2009
DOI: 10.1016/j.fct.2009.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute alcohol consumption and vitamin E co-treatment on oxidative stress parameters in rats tongue

Abstract: The aim of this study was to evaluate the effects of acute alcohol consumption and vitamin E co-treatment upon oxidative stress parameters in rats tongue. Thirty-eight, Wistar rats were separated into five groups (alcohol, alcohol/vitamin E, control, Tween, vitamin E). Alcohol and alcohol vitamin E groups had the standard diet, and 40% alcohol on drinking water. Other groups were fed with the same standard diet and water ad libitum. Vitamin E was given by gavage to vitamin E and alcohol/vitamin E rats twice a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Carrard et al [35] suggested that short-term alcohol consuming modifies the cellular lipid metabolism. Long period of alcohol administration should be achieved in order to determine the chronic effects on rat tongue mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Carrard et al [35] suggested that short-term alcohol consuming modifies the cellular lipid metabolism. Long period of alcohol administration should be achieved in order to determine the chronic effects on rat tongue mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term exposure to alcohol induces changes in the redox balance (Carrard et al, 2009) and an increase in cell proliferation appears later, possibly as a consequence of longer periods of biochemical imbalance. Based on the data obtained in the present study, we suggest the involvement of hydrogen peroxide on cell proliferation, but not in relation to the increase in alcohol-related epithelial proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon could be one of the mechanisms associated with the alcohol-mediated increase in cell proliferation rates (Valentine et al, 1985;Maito et al, 2003;Carrard et al, 2004) as well as the risk of oral cancer attributed to alcohol (Guyton & Kensler, 1993;Klaunig & Kamendulis, 2004). A previous study (Carrard et al, 2009) suggested that even a short term exposure to alcohol induced biochemical disturbances in oral mucosa of rats. In addition, Nrf2, a redox-sensitive transcription factor involved in antioxidant defenses which is usually associated to the response to xenobiotics (Motohashi & Yamamoto, 2004), could be involved in the pathogenesis of alcohol-induced cell and tissue damage.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of these studies indicated that intermediate layer cells are responsible for increased cell proliferation, and no change was observed in basal layer cells in any group since these cells are constantly undergoing physiological division. Therefore, when there is a greater demand for cell replacement, intermediate layer cells, which normally do not proliferate very actively, show increased proliferative activity [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%